Searching for Islamic Perspectives on Livelihood Theory: Insights from Al-Ghazali and Al-Shaybani - Possumah, Bayu Taufiq (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The main purpose of this study is to explore livelihood theory in the works of al-Ghazali and al-Shaybani, presenting it as an alternative to mainstream livelihood conceptions by highlighting its normative impacts on current socio-economic situations. Through textual evidence, this study demonstrates that both scholars viewed livelihood not merely as a means to income and consumption, a perspective that fails to grasp the importance of livelihood as an end in itself and as a means to well-being. Al-Ghazali and al-Shaybani emphasized that livelihood involves affiliating individuals with social responsibilities, which encompass multidimensional variables (religious, legal, moral, political, social, economic, etc.) that influence each other. In light of this, the study proposes to evaluate the potential impact of their ideas on the latest theoretical developments in livelihood and economic science.